Merger C4.5 Algorithm and Adaboost for Determining the Department IPA Students Graduation in SMA Islam Sultan Fatah Wedung Demak - Mochamad Subchan Mauludin; Laily Hermawanti (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
C4.5 algorithm is one of the proposed algorithms by data mining researchers in the field of education for example, determine students' graduation. School is a place of education for children. Various school is kindergarten, elementary school, junior high, high school, universities and others. In high school are usually the success of the National Examination and the Examination Schools a school is determined by the values ​​of students in school. If the students in the school resulted in the National Examination and the Examination Schools, which either means that many students in the school who graduate. Therefore, the students' graduation needs to be determined. The algorithms used in this study is the incorporation of C4.5 and Adaboost algorithm to improve the accuracy in determining students' graduation. This study uses the dataset graduate students majoring in science SMA Islam Sultan Fatah Wedung of Demak some 230 data. Attributes this study consisted of a number of participants, participant names, the value of Indonesian, English value, the value of Mathematics, Physics values, values ​​Chemistry, Biology value, and description. Merger C4.5 algorithms and Adaboost using datasets graduation of students SMA Islam Sultan Fatah produces an accuracy of +/- 99.57% 1:30%. Accuracy merger C4.5 and Adaboost algorithm higher than in previous studies to determine students' graduation. Keywords: Algorithm C4.5, Adaboost,, Students, Grades